Development of compressed air powered engine system based on subaru ea71 model - Chen, Rui (2013)
This thesis deals with development of compressed air powered engine system based on Subaru EA71 model. The objective of this thesis is to make a reverse engineering and design of the engine model, and make the computational analysis of the compressed air powered engine working model by using GT-Power. The thesis describes the compressed air technology that addresses the problems of exhaust gas pollution from vehicles, as well as utilization of fossil fuel. The development of the compressed air powered engine model starts with dismantling the original engine, cleaning the engine with petrol, and drawing all the components into Solidworks. Then develop the engine into two working stages that working with gasoline for four cylinders in the first stage and working with compressed air for two cylinders in the second stage. In this thesis, the research focuses on the second stage. Some components such as cylinder heads and cam profile are modified based on the new design. After this, a simulation by GT-Power is run, and computational analysis the performance of new compressed air powered engine. The results indicated the engine performance predictions and key cylinder predictions. The project achieves the objective of reducing the emission of carbon dioxide. However the new model lacks the power output so that continuous research is needed to fully prove the viability of the technology of the compressed air powered engine